2009
DOI: 10.4103/0971-3026.57209
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion MRI in characterizing benign and malignant breast lesions

Abstract: Aims:The aim of this study was to evaluate the role of MRI based diffusion-weighted imaging (DWI) and the apparent diffusion coefficient (ADC) for characterizing breast lesions in Indian patients.Materials and Methods:This prospective analysis was performed between October 2006 and June 2008. It includes 200 patients between the ages of 16 and 80 years with solid breast lesions greater than 1 cm in diameter. Of these 200 patients, 80 underwent breast MRI with contrast and DWI. One hundred and twenty patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 6 publications
4
16
0
Order By: Relevance
“…These results are in concordance with findings of Palle lalitha et al, (8) on 200 patients with breast lesions using MR Mammography with DWI at b value of 0, 500, 1000. According to this study, the sensitivity of ADC values for the detection of malignant lesions was 97.22% and the specificity was 100% and the positive predictive value was 100% and the negative predictive value was 99%.…”
Section: Diffusion Weighted Imaging and Adc Valuesupporting
confidence: 82%
“…These results are in concordance with findings of Palle lalitha et al, (8) on 200 patients with breast lesions using MR Mammography with DWI at b value of 0, 500, 1000. According to this study, the sensitivity of ADC values for the detection of malignant lesions was 97.22% and the specificity was 100% and the positive predictive value was 100% and the negative predictive value was 99%.…”
Section: Diffusion Weighted Imaging and Adc Valuesupporting
confidence: 82%
“…Palle and Reddy (2009) found that the ADC value obtained with low b-values (0 and 150 s/mm 2 ) is higher than that obtained with higher b-values (499 and 1500 s/mm 2 ) for all lesion types due to contribution of main perfusion effects to the ADC. Therefore, we calculated the ADC value with high b-values (800) to avoid the signal attenuation caused by perfusion effects at low b-values (28).…”
Section: Discussionmentioning
confidence: 60%
“…(7) False negative cases with higher ADC values were encountered in lesions with central necrosis and haemorrhage in a study conducted by Lalithe Palle and Reddy in 200 patients. (5) However, in our study, we did not encounter cases with central necrosis and haemorrhage.…”
Section: Role Of Dwi and Adc In Characterising Benign And Malignant Lmentioning
confidence: 81%
“…(4) Another study done by Lalithe Palle and Reddy et al in 200 patients, the sensitivity of this ADC cut-off for detection of malignant lesions was 97.2% and specificity was 100%. (5) Out of total 50 cases, histopathologically 24 turned out to be benign and 26 were malignant. The mean ADC for benign lesions was 1.7 and for malignant was 1.27.…”
Section: Role Of Dwi and Adc In Characterising Benign And Malignant Lmentioning
confidence: 99%
See 1 more Smart Citation